Evaluation of thermal efficiency in ethanol distillation by solar concentrating parabolic collector - Sumol Sae-heng Pisitsungkakarn; Thansita Thomrungpiyathan (Case Studies in Thermal Engineering)
This research aimed to design, develop and evaluate the thermal efficiency of a solar concentrating parabolic collector (CPC) for distilling ethanol. The area of the CPC was 1.7 m2 with a width and depth of 1.0 m × 1.7 m, respectively. A stainless-steel parabola reflector reflected a concentrating beam onto a rectangular receiver with dimensions of 0.06 m × 0.17 m x 1.00 m (Width x Height x Long). The volume of diluted ethanol was 5000 ml, and the distillation temperature ranged from 84 to 90 °C. This experiment measured two factors: thermal efficiency and distilled ethanol volume with high ethanol concentration. The ethanol distilled from a 20 % diluted solution produced the highest ethanol concentration of approximately 72 % with an ethanol volume of about 260 ml, while the highest thermal efficiency of the solar collector was 20.36 % at 11:00. In brief, the first case resulted in the maximum thermal efficiency of 13.72 % and the best ethanol distillation, with a distilled ethanol volume of about 31 ml. In addition, replacing the material of the solar collector increased the thermal efficiency and distilled ethanol volume from the first case by 9.33 % and 32.26 %, respectively.